Representasi Wajah Masyarakat Gunung Kidul dalam Film Pendek Njagong: Perspektif Meanings and Media - Sunaryanto Sunaryanto; Ahmad Rofi Syamsuri (Metacommunication: Journal of Communication Studies, 2025)
This research critically analyzes the representation of the Gunungkidul community in the short film Njagong. Employing a qualitative method with a critical paradigm from media and cultural studies, this study applies Gill Branston and Roy Stafford’s textual analysis. This framework investigates four concepts: semiotics, structuralism, denotation/connotation, and ideological codes. Semiotically, signifiers like bamboo houses, traditional utensils (e.g., kukusan, irik), dry fields, and salt connote poverty, constructing a social meaning of enduring impoverishment. Structurally, the film depicts a community without class division, where everyone exists in the same social stratum—impoverished farmers working barren land. Connotatively, rural women are portrayed as underdeveloped due to limited education access. The region itself is constructed as barren, dry, and non-modern, suggesting it is unfit for habitation. These representations are reinforced through ideological codes and myths: that villages are too harsh for a proper life and that rural women, expected to marry young, do not require higher education. This study contributes to media and cultural studies by demonstrating how rural representation in film extends beyond depicting material conditions to actively perpetuating ideologies and myths that sustain social inequality. It enriches the discourse on how film can simultaneously reproduce and critique stigmas against marginalized regions. Ultimately, the research underscores the importance of a critical perspective in viewing media as a contested arena where local identity negotiates with dominant discourses of poverty, gender, and modernity.